2011
DOI: 10.1371/journal.pone.0018522
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Jak2 Catalytic Function by Peptide Microarrays: The Role of the JH2 Domain and V617F Mutation

Abstract: Janus kinase 2 (JAK2) initiates signaling from several cytokine receptors and is required for biological responses such as erythropoiesis. JAK2 activity is controlled by regulatory proteins such as Suppressor of Cytokine Signaling (SOCS) proteins and protein tyrosine phosphatases. JAK2 activity is also intrinsically controlled by regulatory domains, where the pseudokinase (JAK homology 2, JH2) domain has been shown to play an essential role. The physiological role of the JH2 domain in the regulation of JAK2 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 55 publications
4
29
0
Order By: Relevance
“…5). The wild-type pseudokinasekinase construct was ∼100-fold less active than the kinase domain alone, recapitulating a similar effect reported for JAK2 (14) and indicating that the pseudokinase has a direct role in inhibiting TYK2 enzymatic activity. Comparison of the four TYK2 analogs that mimic JAK-associated mutations showed that all of the mutants were more active than wild type pseudokinasekinase, with the R744G and R901S mutants approaching levels of activity seen for the isolated kinase domain (Fig.…”
Section: Tumor-derived Jak Mutations Cluster Near the Pseudokinase-kisupporting
confidence: 74%
See 3 more Smart Citations
“…5). The wild-type pseudokinasekinase construct was ∼100-fold less active than the kinase domain alone, recapitulating a similar effect reported for JAK2 (14) and indicating that the pseudokinase has a direct role in inhibiting TYK2 enzymatic activity. Comparison of the four TYK2 analogs that mimic JAK-associated mutations showed that all of the mutants were more active than wild type pseudokinasekinase, with the R744G and R901S mutants approaching levels of activity seen for the isolated kinase domain (Fig.…”
Section: Tumor-derived Jak Mutations Cluster Near the Pseudokinase-kisupporting
confidence: 74%
“…Because the TYK2 kinase activation loop is found in an active conformation in our structure, activation loop phosphorylation likely does not have a role in regulating pseudokinase-mediated inhibition. Given that isolated JAK kinase domains are significantly active (14,32,37) and pseudokinase-kinase interface mutations increase kinase activity, we speculate that, in the context of receptor-induced JAK dimerization, a displacement event, direct or perhaps allosteric, relieves the inhibitory influence of the pseudokinase domain, allowing the kinase domain to autophosphorylate and become the active phospho-transfer catalyst required for downstream signaling.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…24 Using the recently solved crystal structure of JH1-JH2 from TYK2, this intramolecular inhibitory interface has been localized near the JH1 catalytic site and is predominantly mediated by the N-lobes of each domain. 25 The JH1-JH2 crystal structure of TYK2 supports an in cis mode of inhibition with the pseudokinase domain inhibiting the directly adjacent kinase domain within the same protein.…”
mentioning
confidence: 99%